Efektivitas Jobsheet Variable Speed Drive pada Proses Pembelajaran Instalasi Motor Listrik - Randi Eka Putra; Hendri Hendri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This research is motivated by the large number of students who have not achieved learning outcomes, one of the reasons is that learning media still uses worksheets, which results in students not understanding the electric motor installation practicum using VSD. This study aims to determine the effectiveness of electric motor installation jobsheets using VSD at SMKN 1 Sumatera Barat. Student learning outcomes are still low due to learning media factors that are not diverse in creating interest in learning and guiding students' active roles. Therefore, it is necessary to do research on the application of learning media in the form of job sheets to see the effectiveness of student learning outcomes. The type of experimental research that categorizes pre-experimental design uses the Pretest-Posttest Control Group Design. The subjects of this study were class XII TITL students at SMKN 1 Sumatera Barat in the 2023 academic year consisting of 18 students. Collecting data using a test instrument in the form of objective questions. Initial pretest values are generated from daily test scores and posttest scores as data after applying the learning jobsheet. The data obtained were analyzed using classical completeness, Effect Size, and Normalized Gain. The results showed that the average pretest score was 72.00 and the posttest average value was 81.41. The classical completeness score exceeds the minimum score of 88.8%. Meanwhile, the value obtained by the Effect Size is 1.28 in the large category. Effect size shows the magnitude of the influence of a treatment on two variables and is the most important unit of research results. The N-Gain value is obtained with moderate criteria. From the results of the above study, it can be concluded that the jobsheet for Electric Motor Installation Using VSD is effectively used as teaching material in the subject of Electric Motor Installation Using VSD at SMKN 1 Sumatera Barat.